2013
DOI: 10.1161/atvbaha.113.301783
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2–Blocking Antibodies Promote Angiogenesis and Induce ERK1/2 and AKT Signaling via CXCR4 in Endothelial Cells

Abstract: Objective-Toll-like receptor 2 (TLR2) inhibition by function blocking antibodies (ABs) is associated with enhanced preservation of endothelial cell function during vascular disease. In the present study, we investigated the capacity of TLR2-blocking ABs to modulate the angiogenic response of endothelial cells in vitro and in vivo. Approach and Results-Incubation of endothelial cells with mono-or polyclonal anti-TLR2 ABs resulted in increased tube formation, sprouting, and migration of endothelial cells compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…In addition, infected TLR2 KO mice exhibited a pro-angiogenic response with continuous accumulation of neutrophils on Day 21 post-infection, whereas the importance of TLR2/MyD88 signal in angiogenic response to oxidative stress was previously demonstrated (West et al, 2010). Such TLR2 deficiency-dependent pro-angiogenic response was also observed in an ischemia model (Wagner et al, 2013). In a previous report, ischemiainduced tissue necrosis was observed only in TLR2 KO but not in wild-type and TLR4 KO mice (Sachdev et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, infected TLR2 KO mice exhibited a pro-angiogenic response with continuous accumulation of neutrophils on Day 21 post-infection, whereas the importance of TLR2/MyD88 signal in angiogenic response to oxidative stress was previously demonstrated (West et al, 2010). Such TLR2 deficiency-dependent pro-angiogenic response was also observed in an ischemia model (Wagner et al, 2013). In a previous report, ischemiainduced tissue necrosis was observed only in TLR2 KO but not in wild-type and TLR4 KO mice (Sachdev et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…From these data the authors conclude that TLR2 blocking might serve as a promising therapeutic approach in e.g., MI or peripheral artery disease by promoting revascularization. However, considering angiogenesis pro-atherogenic, TLR2 blocking might have detrimental consequences in the context of plaque stability and development, as already mentioned above (Wagner et al, 2013). Nevertheless, it was also shown that the inflammatory mediators IFN-γ and TNF-α decrease CXCR4 and CXCL12 expression in HUVECs, thereby decreasing their angiogenic capacity (Gupta et al, 1998; Salvucci et al, 2004).…”
Section: The Cxcl12/cxcr4 Axis In Cad: Identifying Potential Functionmentioning
confidence: 87%
“…Hyperlipidemia induces this regional endothelial TLR2 expression in LDLR -/-mice, which is associated with early atherosclerosis in lesion-prone areas of the mouse aorta (83). Wagner NM et al further find that inhibition of TLR2 by TLR2-blocking antibodies is beneficial to endothelial cell function in vascular disease (121). In addition, migration of VSMCs also contributes to the development of atherosclerosis.…”
Section: Tlrs and Cardiovascular Diseasesmentioning
confidence: 97%